2021
DOI: 10.1088/1361-6498/ac31a2
|View full text |Cite
|
Sign up to set email alerts
|

Review of extremity dosimetry in nuclear medicine

Abstract: The exposure of the fingers is one of the major radiation protection concerns in nuclear medicine (NM). The purpose of this paper is to provide an overview of the exposure, dosimetry and protection of the extremities in NM. A wide range of reported finger doses were found in the literature. Historically, the highest finger doses are found at the fingertip in the preparation and dispensing of 18F for diagnostic procedures and 90Y for therapeutic procedures. Doses can be significantly reduced by following recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 86 publications
(310 reference statements)
0
13
1
Order By: Relevance
“…The calculated median CFs suggest that physicians should correct the middle and ring doses by at least a factor of 5 and 6 respectively, preferably located on the ND hand, and nurses by a factor of 3 and 4 respectively, irrespective of the hand. To the best of our knowledge, and according to Kollaard et al (23) only one publication has reported on dose ratios (49), obtaining a value of 1.6, which is very different from our results. However, this value was calculated by averaging the dose rates over the three measured ngers (thumb, index and middle), which may underestimate the maximum CFs.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The calculated median CFs suggest that physicians should correct the middle and ring doses by at least a factor of 5 and 6 respectively, preferably located on the ND hand, and nurses by a factor of 3 and 4 respectively, irrespective of the hand. To the best of our knowledge, and according to Kollaard et al (23) only one publication has reported on dose ratios (49), obtaining a value of 1.6, which is very different from our results. However, this value was calculated by averaging the dose rates over the three measured ngers (thumb, index and middle), which may underestimate the maximum CFs.…”
Section: Discussioncontrasting
confidence: 99%
“…The clear patient bene ts of PRRT with 177 Lu-DOTATATE have inevitably increased the number of interventions and studies on this isotope and its theragnostic couples, such as 68 Ga-DOTATOC (12,23,37). However, there are still some challenges regarding its use, such as lack of trained personnel or fully standardised procedures (12), which may result in high doses to the NM staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known for a long time that in the case of nuclear medicine procedures, the hands of personnel are the most exposed parts of the body (Kollaard et al 2021). This is because employees typically do not only carry out the procedures of producing the radionuclides by themselves, but also label chemical compounds with these radionuclides in order to obtain radiopharmaceuticals, and/or inject the prepared radiopharmaceutical into a patient's body (Stuarto 1990;Chiesa et al 1997;Williams et al 1990;Batchelor et al 1991;Dhanse et al 2000;Kubo & Mauricio 2014;Sandouqa et al 2011;Leide-Svegborn 2011).…”
Section: Introductionmentioning
confidence: 99%
“…T hermoluminescence (TL) materials are used for radiation dosimetry in a wide variety of applications such as personal dose readers, environmental sensing, clinical dosage monitoring, etc. [1][2][3] Most TL dosimeters (TLD) are based on the crystalline LiF, single or multi-doped with Mg, Ti, Cu, and P. [4][5][6] Despite the mature development of this compound, there is a need to look for alternatives, on the one hand, because there are limited Li resources while Li demand is strongly rising for other emerging applications such as Li-ion batteries of electric automobiles, and on the other hand, due to the high production cost of a complexly multi-doped fluoride.…”
mentioning
confidence: 99%